A STUDY OF HUMAN RESOURCE MANAGEMENT POLICIES AND PRACTICES AND EMPLOYEE COMMITMENT: EVIDENCE FROM NIGERIAN SMALL AND MEDIUM ENTERPRISES (SMES) - Oginni, Babalola (Annals of Spiru Haret University. Economic Series, 2023)
The study investigated HRM policies and practices on employee commitment to determine their relationship and effects on employee commitment using the SMEs in the South-West, Nigeria as the unit of analysis. The study identified recruitment and selection, training and development, compensation and reward systems, performance appraisal, working conditions, and employee participation as the prevailing HRM policies and practices in the SMEs and singled out compensation and reward systems, working conditions, and employee participation. A multi-sampling technique and survey research method was adopted while copies of questionnaires were administered to 369 respondents. It was found that there exists a positive relationship between HRM policies and practices and employee commitment while compensation and reward systems, working conditions, and employee participation in decision-making have more effects than other variables and R2 of 76% can also explain the variation on employee commitment. It was concluded that among all the activities embarked upon by the SMEs, in South-West, Nigeria towards the attainment of business objectives, HRM policies, and practices have a more significant effect on employee commitment most especially compensation and reward systems, working conditions, and employee participation. Thus, recommended that reward systems should be made competitive through environmental surveys and objectivity should prevail in the practice of the HRM policies.